2014
DOI: 10.1016/j.ygyno.2013.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer control for Hispanic women in Texas: Strategies from research and practice

Abstract: Purpose Hispanic women in Texas have among the highest rates of cervical cancer incidence and mortality in the country. Increasing regular Papanicolaou test screening and HPV vaccination are crucial to reduce the burden of cervical cancer among Hispanics. This paper presents lessons learned from community-based cervical cancer control programs in Texas and highlights effective intervention programs, methods and strategies. Methods We reviewed and summarized cervical cancer control efforts targeting Hispanic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…This research study supports previous research [125] and the importance of academic-community partnerships in the successful delivery of community-based cancer control programs that reach and impact Latina women. Results demonstrated that recruitment, intervention, and assessment methods were feasible and accepted by the target community.…”
Section: Discussionsupporting
confidence: 89%
“…This research study supports previous research [125] and the importance of academic-community partnerships in the successful delivery of community-based cancer control programs that reach and impact Latina women. Results demonstrated that recruitment, intervention, and assessment methods were feasible and accepted by the target community.…”
Section: Discussionsupporting
confidence: 89%
“…16 Purported reasons for the success of such programs include the recognition that promotoras are part of the community in which they work, they have an understanding of the women with whom they work, they are socially and culturally similar to the population that they aim to reach, and they communicate in a similar language and style. 16,17 Although many programs to increase adherence to Pap testing have used promotora programs, not all have been compared with other approaches; fur-thermore, few have assessed the cost-effectiveness of such programs. Building on the notion that effective, culturally appropriate interventions are critical to reducing the burden of cervical cancer in the Latina population, especially among women living in underserved areas, we tested a 3armed randomized controlled trial examining the effects and cost-effectiveness of a culturally relevant, tailored promotora-led arm, a culturally tailored video intervention arm, and a usual-care arm targeting the use of Pap screening.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to increase cancer screening among Hispanic/Latina women have used various educational strategies including mass media, clinic-based strategies, church-based strategies, and community health workers ( promotoras de salud in Spanish) [21]. One Texas study successfully increased Pap test screening among Hispanic/Latina women in Texas using small media (videos and printed materials) combined with community health worker and navigation approaches [13]. In a different multi-site study, the community health worker intervention AMIGAS trial, 52% of participants not up-to-date with their Pap tests completed them within six months compared with 25% of women in the control group [5].…”
Section: Introductionmentioning
confidence: 99%